Potential for Solar Industrial Process Heat Systems for Tea Drying Applications – A Case Study - Seyitini Luckywell; Enweremadu Christopher (Environmental and Climate Technologies)
An increase in energy consumption especially for industrial applications enhances the uptake of fossil fuels since, they are currently the major sources of industrial process heat and electricity. The need for clean energy technologies is therefore critical, in order to meet the rising energy demand using sustainable energy sources. Solar thermal energy technologies have attracted much attention in terms of research and developmental activities worldwide. The present study seeks to explore the viability of adopting solar thermal technologies at Tingamira - Tanganda Tea estate, Zimbabwe. Data on current sources of heat, daily consumption of process heat and required process temperatures was gathered. Systems advisor model (SAM, version-2021.12.2) was applied to analyse feasibility of linear Fresnel (LF) and Parabolic trough (PT) solar thermal technologies for industrial tea drying. LF system is potentially a better option for producing process heat for low temperature applications. It requires smaller aperture area (360 m2) and a lower initial capital cost of $ 112 860 which is about 8 % cheaper. Also, it yields more energy at lower levelized cost of heat as compared to PT technology when solar multiple is increased up to 2. Replacing wood fuel would reduce the factory carbon footprint by 114 tonnes CO2 annually. Also, potential for sensible rock-bed heat storage systems in the tea factory was assessed. Rock bed sensible TES using natural rocks can avail a viable option for heat storage and about 16 m3 of storage volume would be needed to meet a daily heat demand of 1 MWh.